Pigmented epithelioid melanocytoma: Report of a case and review of 173 cases in the literature - Pai-Shan Cheng; Shih-Sung Chuang; Tseng-Tong Kuo; Feng-Jie Lai (Wolters Kluwer Medknow Publications, 2012)
Pigmented epithelioid melanocytoma (PEM), or animal-type melanoma, is an unusual variant of melanoma which has been reported to have indolent behavior and a relatively good prognosis. We report a 12-year-old girl with PEM on the third finger web of her right hand. Histopathologically, it was composed of heavily pigmented dermal epithelioid and spindled melanocytic tumor cells. A sentinel lymph node biopsy was negative, and no recurrence was noted 1 year later. We reviewed 173 previously published cases of PEM or so-called animal-type melanoma in the literature. Among the 173 cases and our case, extremities were the most common sites of occurrence (52/129, 40.3%), and most of the depth of invasions were Clark level IV and V [76/114 (66.7%) and 33/114 (28.9%), respectively]. Lymph nodes metastasis was noted in 39/89 (43.8%) of the cases being investigated. Only two cases died of the disease with visceral metastasis. Thus, a more advanced level of invasion and the presence of lymph node metastasis did not imply a definitely malignant clinical course, because spreading beyond lymph nodes was rare (5/174, 2.9%). However, long-term follow-up with more cases and further research are needed to fully delineate the true biological nature of this pigmented melanocytic tumor.